SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER OBAT MENGGUNAKAN METODE WEIGHTED PRODUCT - Izzah, Nailul; Ardianik, Ardianik (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
The pharmacy is a place for distributing pharmaceutical supplies (medicines) to the public. As an agency that deals directly with customers and the number of suppliers who want to distribute their goods through the pharmacy, it is necessary to choose suppliers to establish good and profitable cooperation. This research was held at the Sulfa Sulfida Lamongan Pharmacy. The purpose of this study is to design and build a decision support system to select suppliers and their implementation. The method used in supplier selection is a weighted product, where suppliers will be assessed based on price criteria, payment tempo, timeliness of delivery, accuracy in number and service support. The results showed that the weighted product method can be implemented in the decision support system for selecting drug suppliers at the Sulfa Sulfida Lamongan Pharmacy. This is evidenced by the same value between the calculation of the system and manually or in the system. Key Word: decision support system, supplier, weighted product